Kinetics of Cucurbita Moschata Puree Drying with Maltodextrin as Drying Aid - Indah Hartati; Salsa Erna Setiawati; Suwardiyono; Farikha Maharani; Safaah Nur Faizin (Research in Chemical Engineering, 2022)
The objective of this research was to investigate the influence of maltodextrin addition of pumpkin puree drying as well as studied the drying kinetics. Several thin layer drying kinetics model comprised of Page, Lewis, Henderson Pabis, Two Term, Weibull as well as diffusion model were used to studied the behavior of pumpkin drying. The puree drying was conducted by added 15% of maltodextrin on pumpkin puree. The drying temperatures were varied of 60-70 The research result show that temperature influence the pumpkin puree drying in which added with maltodextrin as the drying aid. Pumpkin puree drying with addition of maltodextrin performed at temperature of 70 for 150 minutes is considered as the relatively suitable condition as it gives low moisture ratio of 0.07. The thin layer drying kinetics, Midili, give good fittest to the experimental data followed by Page and Weibull. The effective diffusivity is in range of m/s with the obtained activation energy is 30.36 kJ/mol.